2009
DOI: 10.1073/pnas.0811253106
|View full text |Cite|
|
Sign up to set email alerts
|

Endocytosis is required for E-cadherin redistribution at mature adherens junctions

Abstract: E-cadherin plays a key role at adherens junctions between epithelial cells, but the mechanisms controlling its assembly, maintenance, and dissociation from junctions remain poorly understood. In particular, it is not known to what extent the number of E-cadherins engaged at junctions is regulated by endocytosis, or by dissociation of adhesive bonds and redistribution within the membrane from a pool of diffusive cadherins. To determine whether cadherin levels at mature junctions are regulated by endocytosis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
150
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(167 citation statements)
references
References 32 publications
9
150
0
4
Order By: Relevance
“…Fluorescence recovery after photobleaching of GFP-tagged proteins over EcadFc surfaces showed that the turnover rates of E-cadherin, β-catenin, αE-catenin, and F-actin (Fig. 1E) were within ranges observed at normal MDCK cell-cell junctions (8,18).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence recovery after photobleaching of GFP-tagged proteins over EcadFc surfaces showed that the turnover rates of E-cadherin, β-catenin, αE-catenin, and F-actin (Fig. 1E) were within ranges observed at normal MDCK cell-cell junctions (8,18).…”
Section: Resultsmentioning
confidence: 99%
“…On micropatterned surfaces, EcadFc specifically recruited cellular E-cadherin, αE-catenin, and β-catenin (Fig. 1), all of which had mobilities within the ranges of these proteins at bona fide cellcell contacts in MDCK cells (8,18). Thus despite the relative immobility of the EcadFc substrate, the cellular E-cadherin-catenin complex appeared to be as dynamic as that at normal cell-cell adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…), la protéine étudiée est rendue visible et peut être photoblanchie avec une perturbation minime de son activité. Nous avons exploité largement cette approche pour la mesure de la dynamique de protéines du cytosquelette -actine, myosine, ezrine, cadhérine, caténines [5][6][7] -en la combinant avec trois ingrédients nouveaux. Le premier ingrédient est l'excitation de la fluorescence par un processus d'absorption biphotonique 2 [8], qui a lieu dans un volume très restreint autour du point focal, d'environ 1 μm 3 ( Figure 2D).…”
Section: Nouveaux Outils D'investigation Des Propriétés Dynamiques Deunclassified
“…[5]. Par ailleurs, dans les jonctions adhérentes interépithéliales, les cadhérines qui en sont le principal ingrédient ne restent pas plus de 4 à 5 minutes, alors que ces structures adhésives sont stables bien au-delà de l'heure [7]. D'autre part, les pores nucléaires offrent une très belle structure avec une particularité dynamique remarquable : le pore existe comme un assemblage relativement stable en dehors de la mitose, tandis que ses composants élémentaires, plusieurs dizaines de nucléoporines, n'y résident que pendant des temps limités.…”
Section: Un Ballet Moléculaire Incessantunclassified
See 1 more Smart Citation